Introduction to the counseling profession - Capuzzi, David (Allyn & Bacon, 2004)
This introductory text is perfect for students taking their first course in counseling who are trying to determine if they are well matched to the counseling profession. Introduction to the Counseling Profession is unique both in its format and in its content. This edited text is comprised of state-of-the-art information by recognized experts in their respective areas of counseling. The content provides an excellent overview of the history and foundational aspects of counseling including legal aspects, the importance of the helping relationship, basic skills, requirements for working in specific settings, and the expertise needed for working with special populations. This new edition meets the professional orientation standards outlined by the Council for the Accreditation of Counseling and Related Educational Programs (CACREP) and helps students begin preparing for the NCE Exam